The right to the city: outdoor informal sport and urban belonging in multicultural spaces. Issue 4 (8th August 2022) - Aquino, Kristine; Wise, Amanda; Velayutham, Selvaraj; Parry, Keith D.; Neal, Sarah
ABSTRACT: Studies on 'everyday multiculturalism' and 'lived multiculture' have advanced knowledge on the kinds of inclusive everyday spaces and practices that characterize our culturally complex, mobile and superdiverse cities. This paper expands this agenda by exploring informal sporting and leisure interactions amongst migrant and ethnically diverse urban populations. Embedded in a larger comparative city project that examines how urban environments and wider social structures mediate inclusions and exclusions of urban dwellers, this paper presents a case study of temporary migrant workers in Singapore and their participation in outdoor informal sport. It deploys Lefebvre's notion of 'Right to the City' to understand city dwellers' access to urban resources and their collective ability to democratically inhabit the city. Despite structural constraints imposed on marginalized migrants, the nature of informal sport, the spontaneous coming together to play, creative use of public space and a range of convivial practices, generate a sense of urban belonging.